1996
DOI: 10.1021/jo960397i
|View full text |Cite
|
Sign up to set email alerts
|

Ozonolysis of Highly Methylated 1,2-Bis(methylene)cycloalkanes. Influence of the Methyl Substituents on the Course of the Reaction

Abstract: In the ozonolyses of highly methylated 3,3,4,4,5,5-hexamethyl-1,2-bis(methylene)cyclopentane (1a) and 3,3,6,6-tetramethyl-1,2-bis(methylene)cyclohexane (1b), the epoxidation competed with the cleavage of the C−C double bond, whereas only the latter process was observed in the case of the nonmethylated 1,2-bis(methylene)cycloalkanes 1c,d. Competition experiments revealed that the reactivity of the highly methylated 1,2-bis(methylene)cycloalkanes 1a,b is significantly smaller than that of the nonmethylated ones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…To understand the substituent effect on the direction of the cleavage of PO 4 , ozonolyses of indenes 1a − d were conducted in the presence of trifluoroacetophenone. In this respect, we previously reported that this highly electron-deficient ketone can capture carbonyl oxides very efficiently . When ozonolysis of 1,3-dimethylindene ( 1a ) was undertaken in ether in the presence of 1 equiv of trifluoroacetophenone, aldehyde ozonide 7a was obtained in 72% yield.…”
Section: Resultsmentioning
confidence: 99%
“…To understand the substituent effect on the direction of the cleavage of PO 4 , ozonolyses of indenes 1a − d were conducted in the presence of trifluoroacetophenone. In this respect, we previously reported that this highly electron-deficient ketone can capture carbonyl oxides very efficiently . When ozonolysis of 1,3-dimethylindene ( 1a ) was undertaken in ether in the presence of 1 equiv of trifluoroacetophenone, aldehyde ozonide 7a was obtained in 72% yield.…”
Section: Resultsmentioning
confidence: 99%
“…3-(Benzoyloxy)-2-phenylindene ( 1 ) 4 was prepared by the reported method: white powder; mp 119−120 °C (from CH 2 Cl 2 −hexane); 1 H NMR δ 3.92 (s, 2 H), 7.0−8.3 (m, 14 H); IR 1740, 1255, 1245 cm -1 . The ozonolysis procedures have been previously described …”
Section: Methodsmentioning
confidence: 99%